2022
DOI: 10.1177/0192513x211059831
|View full text |Cite
|
Sign up to set email alerts
|

Marital Quality as a Mechanism Linking Childhood Abuse to Mental Health

Abstract: Childhood abuse has been widely associated with mental health problems in adulthood and marital quality may be one possible mediator. We examine marital quality as a mediator linking childhood abuse to positive affect, negative affect, emotionally reactivity, and aggression. Using data from Midlife Development in the United States (MIDUS), results of structural equation modeling indicate that the indirect effects from childhood abuse to each of the mental health outcomes were significant. Marital quality may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In a meta-analysis, Khaleque [34] found that parental warmth predicted psychological adjustment in children with moderate to large effect sizes. Longitudinal research has shown that low levels of parental warmth in childhood are associated with depression in adulthood [5], feelings of worthlessness [35], mental health problems [36,37], and physical health problems [38]. At the same time, research has found that parental warmth is associated with better mental and physical health in adulthood [7].…”
Section: Childhood Family Environmentmentioning
confidence: 99%
“…In a meta-analysis, Khaleque [34] found that parental warmth predicted psychological adjustment in children with moderate to large effect sizes. Longitudinal research has shown that low levels of parental warmth in childhood are associated with depression in adulthood [5], feelings of worthlessness [35], mental health problems [36,37], and physical health problems [38]. At the same time, research has found that parental warmth is associated with better mental and physical health in adulthood [7].…”
Section: Childhood Family Environmentmentioning
confidence: 99%
“…Several studies have confirmed that both men and women with mental health problems also reported higher rates of marital problems [60][61][62]. Interpersonal theories of mental illness [63,64] purport that mental illness in one spouse may have negative effects on the patterns of interaction and communication between both spouses, thus disrupting routines, generating pressure and burden on the relationship, provoking marital disputes, and reducing the quality of the marital relationship.…”
Section: Plos Onementioning
confidence: 99%
“…This in turn may bolster self-esteem and sense of personal control, which occupy a central place in the stress process framework as personal resources (Aneshensel, 2015). These psychological resources may be particularly protective for individuals with a history of childhood emotional abuse because childhood emotional abuse tends to damage positive self-concept (Wright et al, 2009) and prevent the development of these resources (Berzenski, 2019; Ebbert et al, 2019; Fitzgerald & Esplin, 2022; Maneta et al, 2015; Powers et al, 2009). In addition, individuals who enjoy positive interactions with others may perceive that others will offer assistance needed to cope with childhood emotional abuse.…”
mentioning
confidence: 99%